Geoquímica e geocronologia U-Pb e Sm-Nd dos ortognaisses da região de Pontalina (GO), Brasil - Navarro, Guillermo Rafael Beltrano [UNESP]; Zanardo, Antenor [UNESP]; Conceição, Fabiano Tomazini da [UNESP]; Montibeller, Cibele Carolina [UNESP] (My University, 2013)
Orthogneisses of tonalitic to granodioritic composition with calc-alkaline, metaluminous to peraluminous characteristics crop out at the region of Pontalina. The orthogneisses exhibit negative anomalies of Nb, Ta, P and Ti relative to rare earth elements (REE) and litophile elements, besides low contents of Nb, Ta, Y and Yb, similar to the rocks formed in subduction environments. U-Pb geochronological data show a neoproterozoic (681.5 ± 7.7 Ma) crystallization for the orthogneisses. The Nd isotope data yielded weakly negative to positive εNd(T) (+3.2 up to -0.1), with TDM model ages of ~ 1.2 Ga. The combined geochemical and isotopic data suggest that the protolith of these orthogneisses are representative of neoproterozoic juvenile magmas, probably developed in an island arc system, generated during a ca.700 and 600 Ma event of crustal accretion in the western edge of the São Francisco Craton.

Na região de Pontalina (GO) afloram ortognaisses de composição tonalítica a granodiorítica e caracteríticas calcioalcalinas, metaluminosas a peraluminosas. Exibem anomalias negativas de Nb, Ta, P e Ti em relação a elementos terras raras (ETR) e a elementos litófilos e baixos conteúdos em elementos como Nb, Ta, Y e Yb, similar às rochas formadas em ambientes de subducção. Dados geocronológicos U-Pb mostram que a idade de cristalização desses ortognaisses é neoproterozoica (681,5 ± 7,7 Ma). Os dados isotópicos εNd(T) são fracamente negativos a positivos (+3,2 e -0,1), com idades modelo TDM de ~ 1,2 Ga. Em conjunto, os dados geoquímicos e isotópicos obtidos sugerem que o protolito desses ortognaisses são magmas juvenis, com idade neoproterozoica, formados em um sistema de arco de ilha. Este evento foi desenvolvido, provavelmente, durante um evento de acresção crustal na borda oeste do Cráton do São Francisco entre 700 e 600 Ma.
Geochemistry and geochonology U-Pb and Sm/Nd data of the orthogneiss from Pontalina region (GO), Brazil
Keywords: Geochemistry; Geochronology; Orthogneiss; Goiás magmatic arc; Geoquímica; Geocronologia; Ortognaisse; Arco magmático de Goiás